PENGGUNAAN ALAR DAN BA (Benzyl Adenine) DALAM MEDIA KULTUR JARINGAN KRISAN - Astutik Astutik (BUANA SAINS, 2010)
Alar is one of retardation, which accelerates the growth of aksiler shoots, shortens stem joint and strengthens the stem. Alar addition into the medium is assumed to be able to increase the success of Chrysanthemum tissue culture in quantity and quality. The objectives of the research was to finding the best of media to producing a shorter plantlet and has a big stem diameter and the best of number shoots. The research was done in Biotechnology Laboratory of Agriculture Faculty of Tribhuwana Tunggadewi University of Malang. The research was established on January to Juny, 2009. The research used Factorial Complete Random Design, which consists of 2 factors. Factor I: Concentration of Alar was 0 mg/l (A0), 1.0 mg/l (A1) and 2.0 mg/l (A2). Factor II: Concentration of Benzylzdenine (BA) was 1.0 mg/l (B1), 2.0 mg/l (B2) and 3.0 mg/l (B3). There were 9 treatment combinations and repeated 4 times. The observation done on parameter: when the shoot grows, leaf number, shoot number, plantlet height, stem diameter, when the root grows, root number, and acclimatization success percentage. The result of the research showed that the adding of Alar and BA into Chrysanthemum micro-propagation medium had influence on the all parameters. 2.0 mg/l Alar application combined with 1.0 mg/l BA (A2B1) produced shorter plantlet (2.73 cm), bigger stem diameter plantlet (0.20 cm), and produced a better shoot number (20.25 shoots/explant) by the 10th week of culture